Recent Researches in Education - Publisher, Cambridge Scholars (Cambridge Scholars Publishing, 2018)
The book brings together 49 chapters related to the field of education. The main topics explored here include teacher-student interactions; pre-service teachers; children and play; early childhood education; elements of education; children's rights; digital education; attitudes of students towards the environment; art education; and problem solving skills, among many others. It will attract the attention of researchers, but will also be of great interest to academics, teachers, students and staff in social sciences departments and related researchers.